Strength anisotropy of rolled 11Cr-ODS steel. (December 2016) - Tanno, Takashi; Yano, Yasuhide; Oka, Hiroshi; Ohtsuka, Satoshi; Uwaba, Tomoyuki; Kaito, Takeji
Highlights: Rolled 11Cr-ODS steel contained columnar prior particle boundary (PPB) including lined-up Ti-rich precipitates along the rolling direction. The anisotropy of the tensile strength was negligible, though the creep strength in transvers direction was lower than that in longitudinal direction. The results of observations indicated that the slip deformation concentrated on PPB, and the massive break on PPB occurred in transvers direction creep test. The PPB would affect the strength at a stress level lower than the dispersion strengthening threshold stress. Abstract: Materials for core components of fusion reactors and fast reactors, such as blankets and fuel cladding tubes, must offer the best possible high temperature strength and irradiation resistance because they will be exposed to high heat flux and heavy neutron irradiation. Japan Atomic Energy Agency (JAEA) has been developing 9 and 11 chromium (Cr) oxide dispersion strengthened (ODS) steels as candidate materials for advanced fast reactor cladding tubes. In this study the JAEA 11Cr-ODS steel was rolled in order to evaluate its anisotropy. The tensile tests and creep tests were carried out at 700 °C in longitudinal and transverse orientations. The anisotropy of the tensile strength was negligible, though that of the creep strength was distinct. The observation results and chemical composition mapping suggested that the cause of the anisotropy in the creep strength was a previously formed columnar boundary, that is, a prior particle boundary including Ti-rich sub-micro metric precipitates.